A study of the present and potential contribution of dietitians to health care in Australia. - Scott, Jane A. (Curtin University, 1987)
This study was undertaken to determine the present and potential contribution of dietitians to health care in Australia. Data were collected from three separate surveys conducted over a 15 month period from September 1984 to December 1985. The first survey, a National Workforce survey, provided a profile of the demographic and employment characteristics of the dietetic profession in Australia. The second survey was undertaken to determine the role of the dietitian as perceived by dietitians themselves and in the third survey a group of general practitioners was surveyed to determine what they perceived to be the role of the dietitian and to what extent they utilised the services of dietitians.Results of the surveys suggest that dietitians in Australia are not realising their full potential contribution to health care. Firstly, there are too few dietitians in Australia and it is unlikely, despite the best intentions, that the profession will be able to meet consumer need and demand for nutritional care and education. There was considerable disparity between what dietitians considered to be their ideal role versus their actual role. Role disparity among dietitians was highest for professional development, education and research activities and low or moderate for nutritional care activities. A lack of time was most frequently cited as the major deterrent preventing dietitians performing activities which they perceived to be part of their ideal role.The results of the third survey indicated that in general, the doctors surveyed had favourable opinions of dietitians but that they held rather traditional views of the role of the dietitian, expecting them to be more involved in food preparation and service than dietitians expected to be. This general lack of awareness of the role and expertise of dietitians and their potential contribution to health care is likely to lead to an under- utilisation of the full range of services provided by dietitians as evidenced by this study.